Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1111/ecoj.12449
|View full text |Cite
|
Sign up to set email alerts
|

Limited Commitment and the Demand for Money

Abstract: Understanding money demand is important for our comprehension of macroeconomics and monetary policy. Its instability has made this a challenge. Common explications for the instability are financial regulations and financial innovations that shift the money demand function. We provide a complementary view by showing that a model where borrowers have limited commitment can significantly improve the fit between the theoretical money demand function and the data. Limited commitment can also explain why the ratio o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…The results from this literature are ambiguous. 9 To our knowledge, only three papers have so far investigated the implications of a FTT on welfare: 10 Subrahmanyam (1998), Dow and Rahi (2000) and Dávila (2015). Subrahmanyam (1998) develops a two-period rational expectations model with noisy observations using the Kyle (1985) framework.…”
Section: Literaturementioning
confidence: 99%
“…The results from this literature are ambiguous. 9 To our knowledge, only three papers have so far investigated the implications of a FTT on welfare: 10 Subrahmanyam (1998), Dow and Rahi (2000) and Dávila (2015). Subrahmanyam (1998) develops a two-period rational expectations model with noisy observations using the Kyle (1985) framework.…”
Section: Literaturementioning
confidence: 99%
“…The calibration results for Canada are shown in Table 2. U.K. For the U.K., we use quarterly data from the first quarter of 1960 to the third quarter of 2016. Since we could not find a quarterly inflation time series back to 1960, we follow Berentsen et al (2018) and choose β = (1 + r) −1 = 0.968. Also for the U.K., our modelling approach allows us to improve the combined fit of money demand and unemployment when compared with BMW, although to a lesser extent.…”
Section: Robustnessmentioning
confidence: 99%
“…The study found that companies' demand for private security makes an impact on the aggregate demand for money, but remotely and further demonstrated the indirect channel between crime and money arising from market externality. Berentsen et al (2016) strengthened the money demand in a micro-founded monetary model by introducing limited commitment to repay loan factor. They posit that depending on monetary policy, limited commitment will create endogenous borrowing constraint thereby influencing the shape of the money demand curve.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Using Barro (1990) spending model, real GDP is decomposed into the government and private sectors to properly measure the influence of government spending on real balances demand (Ebadi, 2018). In accordance with what is generally done in literature involving variable selection and the framework choice to estimate the demand for real balances, this paper has introduced two scale variables in the model namely public spending and capital stock., This is combined with financial innovation and opportunity costs determinants of holding real balances and includes interest rate, inflation, and exchange rate (Groessl and Tarassow, 2015;Berentsen et al, 2017;El-Rasheed et al, 2017;Ebadi, 2018;Gerlach and Kugler, 2018;Kayongo and Guloba, 2018;Tule et al, 2018). In light of the intuition from empirics, this paper will apply the Autoregressive Distributed Lag (ARDL) cointegration technique to estimate the long-run relationship between variables in the model.…”
Section: Introductionmentioning
confidence: 99%